A qualitative assessment of key considerations for drug checking service implementation - Chloe Grace Rose; A. Simon Pickard; Victoria Kulbokas; Stacey Hoferka; Kaitlyn Friedman; Jennifer Epstein; Todd A. Lee (Harm Reduction Journal, 2023)
Abstract Background With many drug-related deaths driven by potent synthetic opioids tainting the illicit drug supply, drug checking services are becoming a key harm reduction strategy. Many drug checking technologies are available, ranging from fentanyl test strips to mass spectrometry. This study aimed to identify key considerations when implementing drug checking technologies and services to support harm reduction initiatives. Methods Key informant interviews were conducted with harm reduction stakeholders throughout Illinois. Participants included members of existing drug checking services and recovery centers. Interviews were recorded, transcribed, and coded by two researchers using the framework method. Findings were contextualized according to micro (client)-, meso (organization)-, and macro (policy)-level themes. Results Seven interviews were conducted with ten participants. Fourier transform infrared spectroscopy was consistently identified as a technology of choice given its accuracy, range of substance detection, portability, and usability. Recommendations included the use of confirmatory testing, which can help address the limitations of technologies and provide a mechanism to train technicians. Locations of drug checking services should maximize public health outreach and leverage existing harm reduction agencies and staff with lived experience, who are critical to developing trust and rapport with clients. Criminalization and loss of privacy were major concerns for clients using drug checking services. Additional issues included the need to raise awareness of the legitimacy of services through public support from governing bodies, and funding to ensure the sustainability of drug checking services. Conclusions This research facilitated the identification of issues and recommendations from stakeholders around key considerations for the adoption of drug checking technologies, which not only included the cost and technical specifications of instrumentation, but also broader issues such as accessibility, privacy, and well-trained personnel trusted by clients of the service. Successful implementation of drug checking services requires knowledge of local needs and capacity and an in-depth understanding of the target population.